Photovoltaic solar system for a smart bus shelter at Faro Airport - Sousa, Nelson (2022)
In this work, a photovoltaic system solution is studied for power-supply in an accessible and smart bus stop. In addition to lighting, the bus stop is equipped with a digital kiosk and a computer system to offer information to passengers and provide aid to people with reduced mobility. Several approaches in the integration of photovoltaic energy have been explored, demonstrating that the best solution is not a stand-alone system, but a smaller photovoltaic installation with the backing of the public power grid for periods of low photovoltaic production. The conclusions presented are based on economic analysis and environmental performance, particularly on avoided CO2 emissions, in order to ensure the sustainability of the recommended solution.